Sustainability and CDM projects in the Brazilian sugar cane sector: a discussion on the economic-financial aspects - de Souza, Zilmar Jos [UNESP] (IEEE, 2008)
The study discusses how the revenue from the sale of Certified Emission Reductions (CERs) can contribute to the attractiveness of investment in projects of bagasse-based cogeneration. It was observed that revenue from CERs is probably not enough to make these investments acceptable in the economic and financial aspect. However, this study speculates that Clean Development Mechanism projects will be strategic to build a positive image concerning the social responsibility and sustainability of the business in the Brazilian sugar cane sector.
Keywords: Brazilian sugar cane sector; bagasse-based cogeneration; Clean Development Mechanism; internationalization; sustainability